High-purity synthesis of scrolled mats of multi-walled carbon nanotubes using temperature modulation - Kakade, Bhalchandra A.; Allouche, Hatem; Mahima, Subhramanyam; Sathe, Bhaskar R.; Pillai, Vijayamohanan K. (Carbon, 2008)
Felt-like mats (6-7 mu m thick) of multimalled carbon nanotubes wrapped into scrolls have been synthesized by chemical vapor deposition from a toluene-ferrocene mixture using a temperature ramp from 680 degrees C to 550 degrees C in hydrogen-argon atmosphere. Thermogravimetric analysis reveals a very low catalyst content of ca. 1.25 wt% in the as-synthesized sample while, X-ray photo electron and Raman spectroscopies suggest the results matching with that of multiwalled carbon nanotubes. Considering, different time scales of various reactions and the diffusion of different reactants and products a tentative base growth mechanism has been proposed as per the available characterization data in conjunction with possible scrolling effects. Thermal expansion effects could explain a tentative mechanism for rolling action of sheets. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron transport mechanisms with activation energies of 0.33 and 1.03 meV corresponding to two temperature ranges respectively. Cyclic voltammetry and electrochemical impedance analysis show a reversible redox behavior due to very low catalyst content and an irreversible etching of the Fe catalyst after acid treatment. (C) 2007 Elsevier Ltd. All rights reserved.